Peripheral Expression of IL-6, TNF-α and TGF-β1 in Alzheimer's Disease Patients - Gamze Güven; Pınar Köseoğlu; Ebba Lohmann; Bedia Samancı; Erdi Şahin; Başar Bilgiç; Haşmet Ayhan Hanağası; Hakan Gürvit; Nihan Erginel-Ünaltuna (Turkish Journal of Immunology)
Objective: Neuroinflammation is involved in the pathology of Alzheimer's disease (AD). Peripheral levels of various inflammatory cytokines are altered during AD pathogenesis. This study aimed to examine the role of peripheral inflammation in AD pathogenesis by measuring serum levels and gene expression of specific inflammatory cytokines in AD patients. Therefore, we analyzed serum interleukin-6 (IL-6) and transforming growth factor-beta 1 (TGF-β1) levels and mRNA expressions of IL-6 and tumor necrosis factor-alpha (TNF-α) in peripheral blood mononuclear cells of AD patients and controls. Materials and Methods: We quantitatively assessed serum IL-6 and TGF-β1 levels in 25 AD patients and 33 age-matched controls using enzymelinked immunosorbent assay. In addition, we evaluated the mRNA expressions of IL-6 and TNF-α in peripheral blood mononuclear cells from 31 AD patients and their respective controls (n=30) via quantitative real-time polymerase chain reaction. Results: AD patients tended to have higher serum IL-6 and TGF-β1 levels compared to the controls, but the difference was not statistically significant. IL-6 and TNF-α mRNA expression was significantly downregulated in AD patients compared to the controls (p=0.000 and p=0.004; respectively). Serum IL-6 and TGF-β1 levels were negatively correlated with age in AD patients (p=0.025, r=-0.467 and p=0.035, r=-0.431; respectively). Conclusion: The outcomes of this study suggest a disruption in the peripheral immune response in individuals with AD. The observed decreased expression of cytokine genes in peripheral leukocytes may indicate a contributory mechanism through which peripheral cytokines influence AD pathogenesis.